2020
DOI: 10.3390/antibiotics9110822
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rapid Diagnostic Meningitis/Encephalitis Panel on Antimicrobial Use and Clinical Outcomes in Children

Abstract: Rapid molecular diagnostic assays are increasingly used to guide effective antimicrobial therapy. Data on their effectiveness to decrease antimicrobial use in children have been limited and varied. We aimed to assess the impact of the implementation of the FilmArray Meningitis Encephalitis Panel (MEP) on antimicrobial use and outcomes in children. In an observational retrospective study performed at Atlantic Health System (NJ), we sought to evaluate the duration of intravenous antibiotic treatment (days of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…While all studies reported the impact of the multiplex ME panel on hospital length of stay, two studies were excluded from the meta-analyses as they did not report enough information to calculate the mean reduction in hospital length of stay [ 15 , 16 ]. Overall, eleven studies reported at least one outcome of interest for inclusion in the meta-analysis [ 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While all studies reported the impact of the multiplex ME panel on hospital length of stay, two studies were excluded from the meta-analyses as they did not report enough information to calculate the mean reduction in hospital length of stay [ 15 , 16 ]. Overall, eleven studies reported at least one outcome of interest for inclusion in the meta-analysis [ 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The publication dates ranged from 2018−2021, and where reported, the data included ranged from January 2010 to April 2019 ( Table 1 ). Study designs varied widely, including retrospective cohort [ 15 , 20 , 22 , 23 ], case-control [ 18 , 19 , 21 ], pre/post (or before/after) interventions [ 24 , 25 , 26 ], cross-sectionals studies [ 15 ], combination designs [ 16 ], and randomized controlled trials [ 25 ]. Observational studies overall were of moderate quality while the single RCT in this review had a high risk of bias ( Supplementary Tables S4 and S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations